The impact of HIV/AIDS on primary school teachers : an investigation into HIV/AIDS linked support systems and resource material that promote positive attitudes - Katsande, Tendayi Juliet (Stellenbosch : University of Stellenbosch, 2009)
Thesis (MPhil (Industrial Psychology))--University of Strellenbosch, 2009.